Pemanfaatan Bintil Akar Kacang Tanah (Arachis hypogaea) sebagai Pupuk Biologi untuk Pertumbuhan Bibit Cabai Rawit (Capsicum frutescens) dalam Upaya Penyusunan Petunjuk Praktikum Fisiologi Tumbuhan II - Andana, Dwi Sri; Jannah, Husnul; Safnowandi, Safnowandi (Biocaster : Jurnal Kajian Biologi, 2023)
Peanut root nodules can be used as a biological fertilizer. Root nodules are roots containing rhizobium bacteria as nitrogen enhancers, which can be used as biological fertilizers. Nitrogen is an element for forming important compounds in cells, including proteins, DNA and RNA. Cayenne pepper production is low due to lack of nutrients, one of which is nitrogen. To meet this need, researchers use peanut root nodules. The aim of this study was to determine the utilization of peanut root nodules (Arachis hypogaea), as a biological fertilizer for the growth of cayenne pepper (Capsicum frutescens), in an effort to prepare plant physiology practical instructions II. This research is included in pure experimental research and development research. The design used was Completely Randomized Design (CRD). Data collection techniques in this study were through observation and documentation methods, then data analysis used One Way Anova. The population consisted of 5 treatments, namely: 1) P.O (Control with 100% soil); 2) P.1 (3 grams of peanut root nodule fertilizer); 3) P.2 (2.5 grams of peanut root nodule fertilizer); 4) P.3 (2 grams of peanut root nodule fertilizer); and 5) P.4 (1.5 grams of peanut root nodule fertilizer), and repeated 4 times. Parameters observed in this study were plant height, number of leaves, leaf length, leaf width, stem diameter, stem length, and total leaf area. The results of the research on plant height parameters showed that the Fvalue < Ftable 0.05, that is, 1.827 < 3.06, the parameter for the number of leaves with the Fcount < Ftable 0.05, namely 1.500 < 3.06, the leaf length parameter with Fcount < Ftable 0.05, that is, 0.478 < 3.06, the leaf width parameter with a calculated Fvalue < Ftable 0.05, that is, 0.053 < 3.06, the stem segment length parameter with a calculated Fvalue < Ftable 0.05, namely , 0.660 < 3.06, parameter of stem diameter with calculated Fvalue < Ftable 0.05 ie, 0.489 < 3.06, and total leaf area parameter with calculated Fvalue < Ftable 0.05 ie 0.489 < 3.06. Based on the results of the study, all observation parameters did not have a significant effect (non-significant). In the development research, 2 expert validators were used, namely teaching material experts, material expert in plant physiology II and the readability test by 15 students. From the results of data analysis of teaching materials experts, the average value was 3.56, and material experts 3.53. As well as the readability test by 15 students an average of 2.98. So that the practical instructions for plant physiology II are feasible to use without revision.